PENGARUH PERLINDUNGAN HUKUM, ORIENTASI ETIKA IDEALISME, ORIENTASI ETIKA RELATIVISME DAN RETALIASI TERHADAP INTENSI WHISTLEBLOWING (SURVEI PADA MAHASISWA UNIVERSITAS NEGERI DI PROVINSI ACEH) - Azhari Effendi; Nuraini Nuraini (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this research is to know the: (1) the influence of legal protection, idealism ethical orientation and relativism ethical orientation simultaneously on whistleblowing intention, (2) the influence of legal protection has on whistleblowing intention, (3) the influence of idealism ethical orientation on whistleblowing intention, (4) the influence of relativism ethical orientation on whistleblowing intention, (5) the influence of retaliation on whistleblowing intention. The population of this study is 395 students from state universities in Aceh province. Sampling technique used was simple random sampling. The data source used in this study is primary data through the distribution of questionnaires to respondents. Data were analyzed using multiple regression analysis with SPSS 20 processing. The result from this research (1) Legal protection, idealism, relativism and retaliation have an influence together (simultaneously) on whistleblowing intentions. (2) Legal protection has a positively influence on whistleblowing intentions. (3) Idealism has a positive effect on whistleblowing intentions. (4) Relativism has not influence on whistleblowing intention. (5) Retaliation has not influence on whistleblowing intention